Fatores de Interação Humano-Computador em Ecossistemas de Software: Um Mapeamento Sistemático de Literatura - Santos, Mariana; Fernandes, Juliana; Villela, Maria; dos Santos, Rodrigo Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Information Systems (IS) have evolved and new business relations have been created in order to achieve emerging demands from different users. Software Ecosystems (SECO) consist of a class of systems that evidences such relations, involving actors and artifacts supported by a common technological platform. Therefore, an emerging network composed of organizations, developers and users over the SECO platform is formed. In this context, human factors become relevant to IS development. In this paper, we aim to identify human-computer interaction (HCI) factors in ecosystems. To do so, we performed a systematic mapping study on the HCI factors observed in software artifacts in SECO. This study is important because it helps researchers and practitioners to know how to motivate developers to keep contributing to an ecosystem platform as well as adding value to a SECO